Have Sovereign Bond Market Relationships Changed in the Euro Area? Evidence from Italy - David Cronin; Peter Dunne (Intereconomics, 2019)
The Italian sovereign bond market experienced considerable disruption in May 2018 and subsequent months amid concerns about the fi scal implications of political developments in Italy. This episode is used to examine relationships among the euro area bond markets some six years after the euro area sovereign bond market crisis of 2009–2012. The main fi nding is that turbulence in a periphery Member State's bond market (in this case, Italy's) continues to have its strongest cross-border effects on other periphery countries' markets, while core Member States react by disengaging from the sovereign bond market where the disruption originates. The core-periphery distinction identifi ed among the 11 euro area Member States during the crisis then remains broadly intact. The implication for policy is that adverse country shocks continue to have asymmetrical effects within the euro area sovereign bond market. An emphasis on the sustainability of national public fi nances remains necessary, both to protect individual sovereigns against adverse market developments and to reduce the spillover of such shocks to other Member States.
Keywords: 330